SMARThealth pregnancy: the development & evaluation of a complex intervention using mobile clinical decision support to screen, refer and manage pregnant women at high risk of future cardiometabolic disorders in rural India - Nagraj, S (2021)
India has witnessed a rapid rise in cardiometabolic diseases (CMDs), and women with high-risk pregnancy conditions including hypertensive disorders of pregnancy (HDP) and gestational diabetes mellitus (GDM) are at increased risk. In rural India, Community Health Workers (CHWs) deliver antenatal care, and are ideally placed to screen at-risk women in their villages. The aims of my thesis were to design, develop and evaluate a contextually-relevant, theory-informed complex intervention to enable CHWs to screen, refer and counsel pregnant women at high risk of future CMDs during their transition between antenatal, postnatal and ongoing healthcare services.